2020
DOI: 10.1002/cbic.201900726
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Enantiocomplementary Epoxide Hydrolases for Asymmetric Synthesis of Aliphatic and Aromatic Diols

Abstract: The use of enzymes in preparative biocatalysis often requires tailoring enzyme selectivity by protein engineering. Herein we explore the use of computational library design and molecular dynamics simulations to create variants of limonene epoxide hydrolase that produce enantiomeric diols from meso ‐epoxides. Three substrates of different sizes were targeted: cis ‐2,3‐butene oxide, cyclopentene oxide, and cis ‐stilbene oxide. Most of the 28 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…The use of NAC frequencies as indication of enzymatic selectivity has been adopted successfully in previous studies on a variety of enzymes. [36][37][38][39][40][41][42]46 For the substrate-range prediction, we found the Rosetta interface energy between the enzyme and the external aldimine form of the query compound to be in agreement with the experimental activities of the whole transamination reaction. Conversely, there was no apparent correlation between the percentage of NACs and the enzymatic activity (results not shown).…”
Section: Scheme 1 Transamination Reaction Mechanism a Asupporting
confidence: 64%
See 3 more Smart Citations
“…The use of NAC frequencies as indication of enzymatic selectivity has been adopted successfully in previous studies on a variety of enzymes. [36][37][38][39][40][41][42]46 For the substrate-range prediction, we found the Rosetta interface energy between the enzyme and the external aldimine form of the query compound to be in agreement with the experimental activities of the whole transamination reaction. Conversely, there was no apparent correlation between the percentage of NACs and the enzymatic activity (results not shown).…”
Section: Scheme 1 Transamination Reaction Mechanism a Asupporting
confidence: 64%
“…Still, the length of the simulations should be long enough to generate conformational sampling of the ground-state region set at the docking stage, but short enough to maintain a conformation close to the initial structure. Our research group has previously shown that ps-scale MD simulations are long enough to allow meaningful counting of binding poses and that running multiple-independent MD simulations is better for sampling than performing a single long simulation. ,,, Additionally, no large difference was found when comparing the ee % obtained from using the top10% or top20% of Rosetta structures for MD simulations (Table S1). Again, only low-energy conformations should be used to avoid working with unfavorable ground states (unfavorable Rosetta interface energies), but the structures should be diverse enough to prevent single outliers from dominating the averaged frequency of NAC conformations.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…An important example is the work of Arnold et al, in which molecular dynamics simulations and Markov models were used to evaluate the effect of a single mutation in a flexible loop region of the nitrating cytochrome P450 TxtE. Recently, Rosetta design and molecular dynamics simulations , with scoring for near-attack conformations along the simulated trajectory ,,, were used to computationally design and rank enzyme variants. Near-attack conformations (NACs) are transient conformations of enzyme–substrate complexes that are close to the transition state.…”
Section: Introductionmentioning
confidence: 99%